Containment of cholera outbreak in a rural community in Rivers State, Nigeria: a case report on health care in danger - Owhonda, Golden; Luke, Anwuri; Ogbondah, Bright Owhondah; Uzosike, Tondor Cleopatra; Nwadiuto, Ifeoma; Abikor, Victor; Wali, Ihuoma Aaron; Onyiri, Victor Oris; Owhondah, Emmanuel; Bobmanuel, Lime Juice (International Journal Of Community Medicine And Public Health, 2023)
Health care in danger (HCiD) is a public health menace affecting patients, healthcare workers, health facility properties/buildings or/and ambulance services due to the violence experienced in the course of accessing healthcare delivery services. This study was a case report of violence against a healthcare worker during the containment of a cholera outbreak in a rural community in Rivers State, Nigeria. The incident was observed between the 3rd to 5th of May 2022, during the containment of a cholera outbreak within the affected rural community. The victim was a frontline healthcare worker and a member of the rapid response team who was abducted while transporting samples to a reference laboratory for diagnostic confirmation. The abductors demanded ransom but the victim was subsequently released after family members bargained with the assailants. Upon release, she received medical care at the state tertiary facility. She continues to render healthcare services to date. As a follow-up, the State security agencies are currently embedded within the PHEOC response at various levels of healthcare. Communities and stakeholders are encouraged to respect and support healthcare and its resources.